DEVELOPMENT OF CANVAS MODEL BUSINESS-BASED COOPERATIVES: IDEAS IN THE DEVELOPMENT OF INDEPENDENT HOUSES OF WORSHIP IN MEDAN CITY - Barus, Elida Elfi; Nasution, Venny Fraya Hartini; Ichsan, Reza Nurul; Syahbudi, Muhammad; Barus, Irwan Irawadi (Strategic Management Business Journal, 2025)
Research background: The Medan City Government has programmed to establish a house-of-worship-based cooperative, namely a mosque with the "Independent Mosque" program, so it needs to receive support from other parties who have an impact. Through Sharia cooperation described by the Cooperatives and SMEs Office as a financial institution that can help small business owners, especially those operating on a small and medium scale, in transactional problems. This is very important to do so that mosque cooperatives can develop and provide benefits for the underprivileged people in the area. Purpose of the article: This study aims 1) To find out and evaluate the effectiveness of mosques in Medan City in terms of community economic empowerment through the establishment of mosque cooperatives. and 2) To find out and analyze  the Sharia Cooperative Business Plan in realizing an Independent Mosque. Methods: The method used in this study is qualitative, with a literature study research approach, from several sources that are considered relevant to the research theme. The data source used is secondary data. The data collection technique is literature, and the data analysis technique used is qualitative descriptive. The majority of customers are MSMEs, resellers, distributors. Value Prepositions include family principles and shuttle services. Revenue Streams come from financing products, payment services, and property. Cost Structures consist of variable and fixed costs.